2014
DOI: 10.1007/s13105-014-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

Sodium fluoride induces apoptosis in the kidney of rats through caspase-mediated pathways and DNA damage

Abstract: Long-term excessive sodium fluoride (NaF) intake can cause many bone diseases and nonskeletal fluorosis. The kidneys are the primary organs involved in the excretion and retention of NaF. The objective of the present study was to determine the effects of NaF treatment on renal cell apoptosis, DNA damage, and the protein expression levels of cytosolic cytochrome C (Cyt C) and cleaved caspases 9, 8, and 3 in vivo. Male Sprague-Dawley rats were divided randomly into four groups (control, low fluoride, medium fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 31 publications
1
28
0
2
Order By: Relevance
“…It has been reported that fluoride can induce DNA damage in the kidney [28,29]. DNA damage generally results in the activation of the ATM-dependent signaling pathway [40].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fluoride can induce DNA damage in the kidney [28,29]. DNA damage generally results in the activation of the ATM-dependent signaling pathway [40].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies estimated damaged DNA and their levels with mice kidneys by the comet assay at different concentrations of NaF (4, 12, 20mg/L; 50, 100, 200 mg/L) [30,31]. Some of these studies revealed that varying degrees of DNA damage in kidney apoptosis were found in renal cells, which induced by 50, 100, 200 mg/L NaF [31]. And several studies proved that DNA damaged in SO 2 induced mice kidney for 7 days (125, 250, 500 mg/kg body weight) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 8-OHdG in serum, urine or tissue was routinely used as a biomarker for DNA damage and carcinogenesis. Previous animal experiment data showed that NaF exhibited genotoxic activity in bone marrow, liver and kidney cells by the comet assay [34][35][36]. Nevertheless, some rodent studies suggested NaF did not result in systemic genotoxic effect in multiple organs, including liver and kidney [37], which had contradiction between these researches.…”
Section: Sub-chronic Fluorosis Caused Oxidative Stress and Dna Damagementioning
confidence: 97%